A core outcome set for clinical trials of Chinese medicine for hyperlipidemia: a study protocol for a systematic review and a Delphi survey - Geng Li; Li Zhou; Wenwei Ouyang; Meiling Xuan; Liming Lu; Xiaoyan Li; Zehuai Wen; Xiankun Chen (Trials, 2019)
Abstract Background Hyperlipidemia, defined as elevated lipid levels, is the primary and major risk factor for atherosclerotic cardiovascular disease. Several studies have evaluated the effects of Chinese medicine (CM) on hyperlipidemia. However, due to the varied designs and methods of these studies, data synthesis has been difficult, restricting the practical value of the findings. Developing a core outcome set (COS) could solve these methodological concerns. In this paper, we report a protocol to develop a COS for CM clinical trials for hyperlipidemia (COS-CM-Hyperlipidemia). Methods The development of COS-CM-Hyperlipidemia will include four stages: (1) a systematic review to identify potential important outcomes—a study advisory group, composed of core stakeholders of hyperlipidemia, will be set up afterwards to evaluate the identified outcomes and a candidate outcome set will be developed accordingly; (2) a panel of experts will be invited to conduct a three-round Delphi survey, so that the experts’ opinions on the importance of outcomes for treating hyperlipidemia with CM will be collected; (3) a consensus meeting with clinicians, patients, and other key stakeholders will be conducted to finalize the items and definitions; and (4) COS-CM-Hyperlipidemia will be promoted and updated. Discussion The development of this COS will improve the design and operation of CM trials on hyperlipidemia, keeping them in compliance with international standards, as well as the comparability and utility of their results. Trial registration The Core Outcome Measures in Effectiveness Trials Initiative (COMET): http://www.comet-initiative.org/studies/details/983. Registered on 25 April 2017.